Rethinking the quality of children’s bilingual story books - Niswatin Nurul Hidayati (Universitas Muhammadiyah Ponorogo, 2020)
Books are one of the learning media for children, in this case, specifically, bilingual books were discussed. Bilingual books are used to introduce children to the world of Indonesian and English as well, where the book is used by teachers or parents to read stories for children. Bilingual books are numerous and easily found in various bookstores and online stores. However, the quality of the books is questionable whether the English translation used in the book is correct. In this short article, the author takes the example of 7 children's bilingual story books with 376 sentences in them. The author found that the majority of translations used were word-by-word translation and with complex translation because of the use of sentences that are too long and the vocabulary was not appropriate to use in that context. In fact, story books should be books that were easily read and understood by both those who read and those who listen. With the complexity of these books, it will be difficult for teachers and parents to read and understand, let alone convey them to children. The author suggested publishers and the government to pay more attention to the quality of books by selecting competent writers in their fields.